2007
DOI: 10.1080/15257770601112762
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3’,5’-cyclic diguanylic acid (cdiGMP) Using 1-(4-chlorophenyl)-4-ethoxypiperidin-4-yl as a Protecting Group for 2’-hydroxy Functions of Ribonucleosides

Abstract: We herein report a convenient synthesis of 3',5'-cyclic diguanylic acid via the modified H-phosphonate approach. The 1-(4-chlorophenyl)-4-ethoxypiperidin-4-yl (Cpep) group was used as protecting group for the 2'-hydroxy functions of ribonucleosides. Complete unblocking of the fully protected 3',5'-cyclic diguanylic acid gave cdiGMP as a homogeneous compound in an excellent yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…Enzymatic c-di-GMP production outperforms chemical synthesis with respect to time, costs and number of chromatographic purification steps [27][28][29][30][31][32][33]. Moreover, most of the chemical syntheses are based on air-and water-sensitive reagents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enzymatic c-di-GMP production outperforms chemical synthesis with respect to time, costs and number of chromatographic purification steps [27][28][29][30][31][32][33]. Moreover, most of the chemical syntheses are based on air-and water-sensitive reagents.…”
Section: Discussionmentioning
confidence: 99%
“…The reported chemical syntheses of c-di-GMP are multistep reactions, which make them time-consuming, expensive and inefficient [27][28][29][30][31][32][33]. Most of them make use of phosphotriester, phosphoamidite or H-phosphonate chemistry based on air-or water-sensitive reagents and involve several chromatographic purification steps.…”
Section: Introductionmentioning
confidence: 99%
“…The c-di-GMP used in this study was chemically synthesized and prepared as a sodium salt as reported previously [18]. Stock solutions of c-di-GMP at 2.2 mg/ml and cyclic guanosine monophosphate (cGMP, Sigma-Aldrich, St. Louis, MA) at 2 mg/ml were prepared in 0.85% saline.…”
Section: C-di-gmp or Cgmp Treatmentmentioning
confidence: 99%
“…Six laboratories, including ours, have reported routes to synthesis of c-di-GMP and a few analogs 815. These approaches use a range of chemistries, with two using phosphate triester chemistry for both the initial coupling and the cyclization,8,12 while the others begin with an amidite911,15 or H-phosphonate coupling,14 and then use a triester9,11,15 or H-phosphonate cyclization 10,14. A common feature of all of these approaches is the small amount of c-di-GMP prepared, with none reporting amounts over 200 mg, and most much less.…”
mentioning
confidence: 99%